2006
DOI: 10.1136/bjsm.2006.030866
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in theHBBgene relate to individual cardiorespiratory adaptation in response to endurance training

Abstract: Objective: The crucial role of haemoglobin in endurance performance has been well documented. We examined whether polymorphisms in the HBB gene modified aerobic capacity. Methods: 102 recruits were trained by running 5000 m three times per week for 18 weeks. Exercise intensity progressively increased from an initial heart rate corresponding to 95% of the individual baseline ventilatory threshold during the first 10 weeks to 105% during the last 8 weeks. The phenotypes measured were running economy and VO 2 max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(30 reference statements)
0
13
1
Order By: Relevance
“…Nine articles [ 20 28 ] used data from the HERITAGE study and five [ 29 33 ] reviewed Caucasian participant data from the Cardiac Rehabilitation and Genetics of Exercise Performance and Training Effect (CARAGENE) study. Five studies examined clinical data from 102 young male and apparently healthy police recruits in China [ 34 38 ]. The remaining samples came from independent clinical studies focusing on apparently healthy but sedentary adults from a variety of ethnicities including Caucasians, Asians, African-Americans, Native American and Hispanics [ 13 , 39 – 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine articles [ 20 28 ] used data from the HERITAGE study and five [ 29 33 ] reviewed Caucasian participant data from the Cardiac Rehabilitation and Genetics of Exercise Performance and Training Effect (CARAGENE) study. Five studies examined clinical data from 102 young male and apparently healthy police recruits in China [ 34 38 ]. The remaining samples came from independent clinical studies focusing on apparently healthy but sedentary adults from a variety of ethnicities including Caucasians, Asians, African-Americans, Native American and Hispanics [ 13 , 39 – 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examined protocols using High Intensity Interval Training (HIIT) [ 28 , 40 ]. The 5 remaining studies trained participants by running at Ventilatory Threshold (VT) [ 34 38 ]. Training intensity was measured using a percentage of VO 2max , Heart Rate Reserve (HRR), VT, Maximal Power (P max ) or Maximum Heart Rate (HR max ).…”
Section: Resultsmentioning
confidence: 99%
“…In turn, intron 2 +16 C/G of this gene may lead to different expression, because it is in the alternative splicing region of mRNA [11, 23]. Simultaneously, it is suggested that the homozygous CC for both polymorphisms could have a higher haemoglobin concentration [11].…”
Section: Discussionmentioning
confidence: 99%
“…The haemoglobin plays a crucial role in endurance performance, because the increase in its concentration in blood is associated with enhanced VO2 max and endurance capacity, which is also proportional to the increase in the oxygen carrying capacity of the blood. Subjects homozygous for intron2, +16C/C or -551C/C in the haemoglobin gene have decreased oxygen cost of running, thus explaining part of the individual variation in the cardiorespiratory adaptation to endurance training 171 . Three quantitative trait loci have been related to glucose and insulin metabolism phenotypes in response to endurance training exercise.…”
Section: Other Gene Related To Fitness Phenotypementioning
confidence: 99%